Surrealist Dreams of Artificial Intelligence: Revisiting Frederick Kiesler's "Endless House" - KARABAĞ, ÇİĞDEM; Tekin, İlke (Interaction Design and Architecture(s), 2025)
The dream world of Surrealism bases itself on critical ways of thinking contrary to the status quo that envision new ways of life. Today, these imaginations are reflected in speculative fiction produced with artificial intelligence (AI) software. Generative AI creates visuals from text using existing digital datasets. AI-generated speculative fiction fosters critical thinking by expanding intellectual boundaries and is a remarkable innovation in human and robot collaboration. The aim in this paper is to examine AI's speculative creation processes and limits of imagination and conduct a comparative analysis through AI reproductions of surrealist spaces. This analysis involves surrealist architect Frederick Kiesler's "Endless House". This two-stage study was conducted with an exploratory case study model using generative AI applications and visual data analysis. The analysis compared the outputs of the Midjourney AI, OpenAI, Leonardo AI, and DALL-E 3 applications, and discussed the exploration process of Midjourney in detail. The findings show that AI's exploration process and limitations depend on how defined the subject is in the prompt text and the meanings and the weight in the databases of the keywords used.
Keywords: Artificial Intelligence; Frederick Kiesler; Midjourney; Speculative Fiction; Surrealism